Efficiency and future generations - Broome, J (Cambridge University Press, 2018)
Standard lessons from economics tell us that an externality creates inefficiency, and that this inefficiency can be removed by internalizing the externality. This papers considers how successfully these lessons can be extended to intergenerational externalities such as emissions of greenhouse gas. For intergenerational externalities, the standard lessons involve comparisons between states whose populations of people differ, either in their identities or their numbers. Common notions of efficiency break down in these comparisons. This paper supplies a new notion of efficiency that allows the lessons to survive, but at the cost of reducing their practical significance.